2022
DOI: 10.1007/s11249-022-01657-5
|View full text |Cite
|
Sign up to set email alerts
|

Frictionless vs. Frictional Contact in Numerical Wear Predictions of Conformal and Non-conformal Sliding Couplings

Abstract: The role of friction on wear evolution is manifold since it interplays with lubrication regime, nominal contact point, and contact pressure distribution. Nevertheless, in the literature many wear models simulate wear assuming frictionless contact conditions to simplify the analyses. That assumption, physically not realistic, often appears as a contradiction, permitted in numerical simulations where friction and wear can be considered independent phenomena.This study aims to validate the frictionless assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the present study, we aimed to: (a) further validate the analytical procedure by comparing our predictions to other studies in the literature from other research groups; (b) solve some discrepancies observed in the first results at the borders of the worn region; (c) prove the reliability of the application and the procedure to frictional contacts, considering our recent FE results described in [14,15].…”
Section: Introductionmentioning
confidence: 72%
“…In the present study, we aimed to: (a) further validate the analytical procedure by comparing our predictions to other studies in the literature from other research groups; (b) solve some discrepancies observed in the first results at the borders of the worn region; (c) prove the reliability of the application and the procedure to frictional contacts, considering our recent FE results described in [14,15].…”
Section: Introductionmentioning
confidence: 72%
“…However, it is incapable of transmitting tensile stresses. For additional information regarding contact modeling with friction, see [44].…”
Section: Finite Element Model and Resultsmentioning
confidence: 99%
“…The contact was assumed as asymmetric as in this case only one body wears out. Moreover, the contact was simulated as frictionless, since the effect of the friction on wear is negligible as demonstrated in [15]. The analysis was solved by means of an Augmented Lagrange algorithm and the nodal-projected normal from contact was adopted as the detection method with the cylinder and plate/disk as the contact and target body, respectively.…”
Section: Contact and Wear Conditionsmentioning
confidence: 99%
“…It is preferred to its inverse that should be considered in the field is worth stressing that when 𝛾 → 0, i.e., → ∞, the PoD → PoP. From Equation ( 16), it can be observed that the ratio is maximum when γ when g(1) = 32/(9π) ≅ 1.132, meaning that the PoD produced higher wear volum 9)- (15).…”
Section: 𝜌 Acos 1 + 𝜌 − 𝛾 2 𝜌 𝑑𝜌 𝛾 𝜋 𝜌 = 𝑅 𝑅mentioning
confidence: 99%